THE ROLE OF THE MINIMUM EQUIPMENT LIST IN IMPROVING AIRCRAFT OPERATIONAL SAFETY AND EFFICIENCY - Tria Reza Putri; Mahatanti Muthia Devi; Gilang Ramadhan; Hadi Prayitno (Jurnal Penelitian, 2025)
The Minimum Equipment List (MEL) is an operator-specific document that establishes the conditions under which an aircraft may temporarily operate with specified instruments, equipment, or systems inoperative. Its implementation is intended to maintain an acceptable level of aviation safety while supporting operational continuity and effective aircraft maintenance planning. This study analyzes the role of MEL in improving aircraft operational safety and efficiency, its contribution to aircraft dispatch and maintenance decision-making, and the implementation challenges identified in aviation regulations and previous studies. A narrative literature review was conducted using international aviation regulations and peer-reviewed studies related to MEL, aircraft maintenance, continuing airworthiness, operational reliability, and aviation safety. The reviewed literature indicates that MEL provides a structured reference for evaluating technical defects, determining dispatch eligibility, applying maintenance and operational procedures, and controlling defect-rectification intervals. Proper implementation may reduce unnecessary aircraft grounding, delays, cancellations, aircraft substitutions, and unplanned maintenance. However, MEL effectiveness depends on regulatory compliance, personnel competence, accurate technical documentation, interdepartmental coordination, and continuous monitoring of deferred defects. MEL should therefore be understood as an integral component of continuing airworthiness, maintenance management, and aviation safety management.